2018
DOI: 10.1038/s41598-018-25734-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a pyrethroid pesticide decomposing esterase gene, Est3385, from Rhodopseudomonas palustris PSB-S

Abstract: Full length open reading frame of pyrethroid detoxification gene, Est3385, contains 963 nucleotides. This gene was identified and cloned based on the genome sequence of Rhodopseudomonas palustris PSB-S available at the GneBank. The predicted amino acid sequence of Est3385 shared moderate identities (30–46%) with the known homologous esterases. Phylogenetic analysis revealed that Est3385 was a member in the esterase family I. Recombinant Est3385 was heterologous expressed in E. coli, purified and characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Cloning was carried out from metagenomic library of soil samples and sequence analysis revealed that 819 bp pye3 gene codes for 273 amino acid protein. Enzyme was further characterized on the basis of enzyme kinetics ( K m and K cat activity) (Li et al, 2008; Luo et al, 2018).…”
Section: Gene Cloning and Enzymatic Characterization Of Pyrethroid Camentioning
confidence: 99%
“…Cloning was carried out from metagenomic library of soil samples and sequence analysis revealed that 819 bp pye3 gene codes for 273 amino acid protein. Enzyme was further characterized on the basis of enzyme kinetics ( K m and K cat activity) (Li et al, 2008; Luo et al, 2018).…”
Section: Gene Cloning and Enzymatic Characterization Of Pyrethroid Camentioning
confidence: 99%
“…Genetic engineering research has been conducted to develop microorganisms that are effective for the biodegradation of pesticides and pesticide residues [47,60,179,205,287]. Hussain and coworkers have reviewed research progress on this topic [111].…”
Section: Remediation Of Pesticidesmentioning
confidence: 99%
“…The carboxylesterase EstSt7 from Sulfolobus tokadaii, has been shown to hydrolyze a variety of synthetic pyrethroids, including type I and type II pyrethroid pesticides (Wei et al 2013). The pyrethroid-degrading gene coding for Est3385 from R. palustris PSB-S was also cloned and expressed using previously published genes (Luo et al 2018). The construction of pesticide-degrading engineered bacteria with broad-spectrum and e cient degradation ability by mining more functional genes has attracted much attention, and will open new avenues for the remediation of environmental pollution.…”
Section: Introductionmentioning
confidence: 99%